2020
DOI: 10.1108/jedt-07-2020-0287
|View full text |Cite
|
Sign up to set email alerts
|

Turnaround project risk assessment using hybrid fuzzy SWARA and EDAS method: case of upstream oil process industries in Iran

Abstract: Purpose The purpose of this paper is to propose a new framework for assessing the risks of turnaround projects in upstream oil process plants. Design/methodology/approach This study represents a new hybrid framework for turnaround project risk assessment. First, according to experts’ opinions, the project risks were identified using interviews and brainstorming. The most important risks selected by experts and a hybrid multiple-attribute decision-making (MADM) method used to assess and prioritize them. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Eirgash et al identified a model using a multi-objective learning-based optimization algorithm for project-scheduling optimization [41]. Moniri et al proposed a model for risk assessment in projects [42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eirgash et al identified a model using a multi-objective learning-based optimization algorithm for project-scheduling optimization [41]. Moniri et al proposed a model for risk assessment in projects [42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is seen that the method has been used especially in research in the field of sustainability in recent years. Looking at the literature, fuzzy SWARA was used by Ansari et al, (2020) to prioritize the criteria for remanufacturing supply chain risks, Moniri et al, (2020) to prioritize the criteria for project risks, Rani et al, (2021) to prioritize the criteria for sustainable supplier selection. Other hand Tas et al, (2021) and Tus & Adalı (2022) used F-SWARA to prioritize the criteria for green supplier selection, Ghasemi et al, (2021) to prioritize the criteria for sustainable health tourism destination.…”
Section: Fuzzy Swara (F-swara)mentioning
confidence: 99%
“…Rani et al [16] used Pythagorean fuzzy numbers on SWARA and VIKOR methods in solar panel selection. Moniri et al [17] selected fuzzy SWARA and fuzzy EDAS methods in order to risk assessment in the oil processing industry.…”
Section: Introductionmentioning
confidence: 99%